The role of social media in shaping academic performance: a case study using multiple linear regression analysis / Nornadiah Mohd Razali ... [et al.] - Mohd Razali, Nornadiah; Azizul Rahman, Nur Aliessa; Hashim, Nur Aqilah; Abdul Hadi, Az’lina; Azid @ Maarof, Nur Niswah Naslina; Azlan, Nuralina (Unit Penerbitan UiTM Kelantan, 2024)
In the era of rapid technological advancement, social media has become an integral part of the daily lives of students, offering a platform for connectivity, information sharing, and self-expression. While these platforms have undoubtedly revolutionised communication and networking, their influence on various aspects of an individual’s life, particularly on academic performance, has been a subject of growing concern and debate. This study delves into the impact of social media on students’ academic performance. The Social Media Addiction Questionnaire (SMAQ) and Social Media Engagement Questionnaire (SMEQ) instruments were adopted to measure social media addiction and social media engagement of the students, respectively. A Cumulative Grade Pointer Average (CGPA) was used to measure students’ academic performance. This study involved a total of 363 students selected from a public university in Malaysia through convenience sampling. A multiple linear regression analysis (MLR) was employed to analyse the impact of social media on academic performance. The results indicated that the time spent on social media per day, tolerance, and intense desire were significant predictors of students’ performance, while impaired control, harmful use, and social media engagement were not significant predictors of students’ performance. This research offers a comprehensive contribution by examining both the theoretical and practical dimensions of social media usage among students. Theoretically, it expands the current understanding of social media addiction by identifying specific dimensions – intense desire and tolerance – that significantly affect academic performance, emphasising the importance of viewing social media addiction as a multifaceted issue rather than a singular problem. It also provides insights into the mechanisms through which excessive social media use can hinder academic outcomes, such as decreased concentration, reduced study time, and increased procrastination.